1993
DOI: 10.1093/oxfordjournals.humrep.a138230
|View full text |Cite
|
Sign up to set email alerts
|

Infertility:Treatment of male infertility: is it effective? Review and meta-analyses of published randomized controlled trials

Abstract: There are few widely accepted treatments for male subfertility. Controlled trials are necessary to evaluate different subfertility treatments because pregnancies and spontaneous improvements in semen parameters occur without treatment. Properly randomized trials can find out whether pregnancy rates are higher or lower than expected after treatment. Quantitative meta-analysis improves precision where individual trials are not powerful enough to demonstrate moderate treatment effects. Only 174 published randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 0 publications
0
23
1
9
Order By: Relevance
“…Dans les oligoasth6nospermies, divers traitements m6di-camenteux ont 4t6 utilis4s, certains sur des bases physiopathologiques incertaines (arginine, zinc, vitamines), d'autres bas4s sur les m6canismes de contr61e hormonal de la spermatog6n6se. Les antioestrog6nes (Clomif'ene -Tamoxif'ene) paraissent avoir une certaine efficacit6, n6anmoins, les r6sultats sont modestes et il faut recourir ~ la m4thode de la m4ta-analyse [35] pour objectiver leur efficacit4. L'irr4gularit6 des effets des anticestrog~nes renforce l'hypoth6se de m4canismes physiopathologiques diff6rents selon les patients.…”
Section: Les Traitements Masculinsunclassified
“…Dans les oligoasth6nospermies, divers traitements m6di-camenteux ont 4t6 utilis4s, certains sur des bases physiopathologiques incertaines (arginine, zinc, vitamines), d'autres bas4s sur les m6canismes de contr61e hormonal de la spermatog6n6se. Les antioestrog6nes (Clomif'ene -Tamoxif'ene) paraissent avoir une certaine efficacit6, n6anmoins, les r6sultats sont modestes et il faut recourir ~ la m4thode de la m4ta-analyse [35] pour objectiver leur efficacit4. L'irr4gularit6 des effets des anticestrog~nes renforce l'hypoth6se de m4canismes physiopathologiques diff6rents selon les patients.…”
Section: Les Traitements Masculinsunclassified
“…Generally, the homeopathy physician does not publish his or her results, nor does he replicate the same technique of treatment for patients with the same disorder. O'Donovan et al [21] conducted a metaanalysis of homeopathic trials for infertility, and concluded that the quality of the majority of trials was poor. Furthermore, it is difficult to evaluate the results of homeopathic treatments in the same manner as conventional treatment as a result of the differing medical principles and differing healing processes underlying each method [22].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors believe that varicocele causes oligospermia by elevating the temperature around the testicles and, therefore, recommend varicocoelectomy in every case of male infertility in which a varicococele is detected (Nieschlag, 1992) A few others disagree and argue that varicocoelectomy has no place in the management of male infertility (O'Donovan et al, 1993). Hence, further studies are required to identify the relationship between male infertility and varicocoeles.…”
Section: Causes Of Infertilitymentioning
confidence: 99%